Selling Procedures with Private Information and Common Values - Lindsey, John H.; Samuelson, William; Zeckhauser, Richard (Management Science, 1996)
The seller posted-price procedure is probably the most common method for making transactions in modern economies. We analyze the performance of posted pricing for transactions having significant common-value elements. In a model of two-sided private information, we characterize the fully revealing, perfect equilibrium offer strategy of the seller. We also characterize equilibrium behavior under two other pricing procedures—a sealed-bid procedure and a direct revelation mechanism. Finally, we examine the efficiency of these procedures and show that as the degree of common values increases, fewer mutually beneficial agreements are attained.